Sosialisasi Pengenalan Mangrove Kepada Siswa SD Negeri Rutong, Ambon - Maluku - Ronald D. Hukubun; Rahman Rahman; Eva Kaimudin; Atmisari Diman; Grace Pattiselanno; Mahriyana Hulopi (Lembaga Pengembangan Kinerja Dosen, 2023)
Rutong Village, located on the South Leitimur Peninsula, Ambon City, has many mangrove plants scattered along the coast. Mangroves have high species diversity and great benefits for the community. The introduction of mangrove socialization aims to introduce the types and benefits of mangroves to the community from an early age. The target of this activity was Elementary School of Negeri Rutong students in grades IV, V, and VI, totaling 30 people. The socialization results were evaluated with a question and answer session to determine students' knowledge after attending the socialization. The results show that the students have recognized several types of mangroves based on the potential in Rutong Village. In addition, the students also became aware of the benefits and importance of protecting the mangrove ecosystem for the life of the aquatic biota in the vicinity.